(untitled) (TAMADDUN NURI JURNALI, 2025)
This article discusses the content of the philosophy of values. The analysis of problems related to the essence and content of values has a long history of gradual development. The harmony of values in the civilization of our homeland has created the basis for the emergence of not one, but two unique renaissances. Today, in parallel with all socio-economic and political reforms, special attention is paid to family values.